Sistem Informasi Pendukung Pengambilan Keputusan Manajemen Pendidikan - Amiruddin, Amiruddin; Nurhasanah, Sania; Saraini, Ihsan; Amalia, Cantika; Ningsih, Pitri Ristia; Febriyan, Rio (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Education Management Information System is a combination of human resources and information technology applications to select, store, process, and retrieve in order to support the decision-making process in the field of education. Researchers realize the importance of adopting information systems practices combined with technological advances. The purpose of this study is to find out how information systems are meant as support for education management decision making. This research uses a descriptive method with a qualitative approach. The results of this study show that the information system supporting education management decision making greatly utilizes all the potential of facilities / facilities and infrastructure as a stepping stone in the application of education management information systems. Stages in Management Information Systems 1). Management Information System Data Collection Process, 2). Management of Management Information Systems, 3) Deployment of Management Information Systems. Specifically, the development of an education driver's license can provide improvements in educational services, namely, policy-making considerations on the customer satisfaction process in a determination of meeting educational quality standards that include basic services and auxiliary services.